Effect of Chlorhexidine and Tea Tree Oil on Reducing the Number of Oral Microorganisms - De Melo Moreno, André Luiz [UNESP]; De Moraes Melo Neto, Clóvis Lamartine [UNESP]; Coelho Goiato, Marcelo [UNESP]; De Araujo Moreno, Nathaly Vilene; Dos Santos, Daniela Micheline [UNESP]; De Lima, Cássia Cunha [UNESP]; Lopes Motta, Rogério Heládio; Ramacciato, Juliana Cama (Thieme, 2024)
Objectives Thus, the aim of this study was to compare the effect of using two preoperative mouthwashes (0.12% chlorhexidine and 0.2% tea tree oil) on the number of colonies of oral microorganisms. Materials and Methods Forty participants who needed to be rehabilitated with dental implants were included in this study. They were randomly divided into two groups (chlorhexidine group and tea tree group; n = 20, each). For each group, saliva samples were collected at four different times: T0 (initially)-before using the mouthwash, T1-after 1 minute of using the mouthwash, T10-after 10 minutes of using the mouthwash, and T60-after 60 minutes of using the mouthwash. At T0 and T1, saliva samples were collected before implant placement surgery, and at T10 and T60, saliva samples were collected during surgery. In each group, one saliva sample was collected at each evaluated time point for each patient, totaling 4 saliva collections per patient. MSB agar (Mitis-Salivarius-Bacitracin) and BHI agar (Brain Heart Infusion) culture media were used in each group. Microbial colony counts were performed using a magnifying glass and recorded in CFU (colony forming units)/mL. Statistical analyses were performed using the Friedman, Mann-Whitney U and Wilcoxon tests (p < 0.05). Results Based on MSB agar culture medium, at T0, the number of Streptococcus mutans colonies in the chlorhexidine group was significantly higher compared with the tea tree group (p <0.05; MSB agar). The chlorhexidine group showed significantly lower CFU/mL values for Streptococcus mutans at T1, T10, and T60 compared with the tea tree group (p <0.05; MSB agar). Based on BHI agar culture medium, at T0, the chlorhexidine group showed a significantly lower value of CFU/mL compared with the tea tree group (p < 0.05; BHI agar). At T1, T10, and T60, the chlorhexidine group showed significantly lower CFU/mL values compared with the tea tree group (p <0.05; BHI agar). Conclusion Chlorhexidine is more indicated as a preoperative mouthwash than tea tree oil, due to its significantly more effective antimicrobial action.
Keywords: chlorhexidine; dental implants; dental plaque; Melaleuca; mouthwashes; Streptococcus mutans; tea tree oil